2022
DOI: 10.1038/s41380-022-01527-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy of cognitive deficits in fragile X syndrome

Abstract: Breaking an impasse in finding mechanism-based therapies of neuropsychiatric disorders requires a strategic shift towards alleviating individual symptoms. Here we present a symptom and circuit-specific approach to rescue deficits of reward learning in Fmr1 knockout mice, a model of Fragile X syndrome (FXS), the most common monogenetic cause of inherited mental disability and autism. We use high-throughput, ecologically-relevant automated tests of cognition and social behavior to assess e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 90 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…To that end, we inject animals with a Tissue Inhibitor of MetalloProteinases (TIMP-1), an enzyme regulating the activity of synaptic plasticity proteins. Changing its physiological levels was previously shown to disrupt the neuronal plasticity in various brain structures [42, 43], including the prefrontal cortex (PFC) [33, 44]. Now, we ask if we can identify changes in behavioral patterns after the mice have been injected with nanoparticles (NP) gradually releasing TIMP-1 (NP-TIMP-1) into the PL [37].…”
Section: Resultsmentioning
confidence: 99%
“…To that end, we inject animals with a Tissue Inhibitor of MetalloProteinases (TIMP-1), an enzyme regulating the activity of synaptic plasticity proteins. Changing its physiological levels was previously shown to disrupt the neuronal plasticity in various brain structures [42, 43], including the prefrontal cortex (PFC) [33, 44]. Now, we ask if we can identify changes in behavioral patterns after the mice have been injected with nanoparticles (NP) gradually releasing TIMP-1 (NP-TIMP-1) into the PL [37].…”
Section: Resultsmentioning
confidence: 99%
“…The biological mechanism behind MMP-9 responses to cochlear implantation remains unclear. It should be noted, however, that experimental studies have shown that both increased and decreased MMP-9 activity produces alterations in synaptic plasticity, learning, and memory [ 44 , 45 ]. In fact, Wiera et al directly demonstrated deficits in LTP (an electrophysiological model of synaptic plasticity) in gene knockout mice lacking MMP-9 activity, as well as in rats overexpressing the MMP-9 gene in neurons [ 46 ].…”
Section: Discussionmentioning
confidence: 99%